2012
DOI: 10.1111/j.1556-4029.2012.02256.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Situs Inversus Found Coincidentally Following a Firearm Injury

Abstract: Situs inversus totalis is very rare and usually diagnosed coincidentally as it does not affect the patient's life. Being unaware of the patient's condition can lead to undesirable results from the surgeon and patient's point of view when an emergency and forensic surgical intervention is required. We present a case who was operated on urgently for a firearm injury after receiving a preoperative diagnosis of situs inversus totalis. In conclusion, situs inversus totalis can cause difficulties for surgeons in cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Nature, velocity, and type of injury, as well as solid versus hollow organ involvement, result in various outcomes [5] , [6] . Indisputably, abnormal location can lead to diagnostic confusion and technical difficulties in surgery [1] , [2] . Normal routine exposure, manoeuvre and handling of the solid organs will be tricky as these types of patients are rare in incidents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nature, velocity, and type of injury, as well as solid versus hollow organ involvement, result in various outcomes [5] , [6] . Indisputably, abnormal location can lead to diagnostic confusion and technical difficulties in surgery [1] , [2] . Normal routine exposure, manoeuvre and handling of the solid organs will be tricky as these types of patients are rare in incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative planning with the anaesthetic team is mandatory in anticipating potential cardiac or pulmonary anomalies [1] . These associated congenital defects can lead to complex complications in polytrauma with multiple injuries [2] , [4] , [7] . Initial management follows a similar advanced trauma life support protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there have only been a few instances where authors have demonstrated utility of plain XR during resuscitation of a gunshot patient, but these are limited to thoracic injuries. 19,20 The use of CT scan to determine trajectory of bullets has been recognized since the 1980s. 21 Magnetic resonance imaging may also be a valuable tool in identifying structures injured by a bullet.…”
Section: Discussionmentioning
confidence: 99%